Deveolpment and testing of a chemical sensor of micro-structured optic fiber for meassuring carbon dioxide concentrations - María Angélica Acosta Pérez; Sir Alexci Suárez Castrillón; Albert Miyer Suárez Castrillón (Tecnura, 2017)
Objectives:  The present study focused on the development of a optic fiber sensor for carbon dioxide (CO2), the measuring of variations of the refractive index of a CO2 medium undergoing controlled changes of temperature and pressure, and comparing this experimental refractive index with a calculated theoretical refractive index.